Prognostic utility of albumin‐bilirubin grade for short‐ and long‐term outcomes following hepatic resection for intrahepatic cholangiocarcinoma: A multi‐institutional analysis of 706 patients. Issue 2 (25th April 2019) - Tsilimigras, Diamantis I.; Hyer, J. Madison; Moris, Dimitrios; Sahara, Kota; Bagante, Fabio; Guglielmi, Alfredo; Aldrighetti, Luca; Alexandrescu, Sorin; Marques, Hugo P.; Shen, Feng; Koerkamp, B. Groot; Endo, Itaru; et al.
Abstract: Background: The objective of the current study was to define the impact of albumin‐bilirubin (ALBI) grade on short‐ as well as long‐term outcomes among patients with intrahepatic cholangiocarcinoma (ICC). Methods: Patients who underwent hepatectomy for ICC between 1990 and 2016 were identified using an international multi‐institutional database. Clinicopathologic factors including ALBI score were assessed using bivariate and multivariable analyses, as well as standard survival analyses. Results: Among 706 patients, 453 (64.2%) patients had ALBI grade 1, 231 (32.7%) ALBI grade 2, and 22 (3.1%) had ALBI grade 3. After adjusting for all competing factors, patients with ALBI grade 2/3 had higher odds of a prolonged length‐ of‐ stay (>10 days, odds ratio [OR] = 2.37, 95% confidence interval [CI]:1.47‐3.80), perioperative transfusion (OR = 2.15, 95% CI:1.45‐3.18) and 90‐day mortality (OR = 2.50, 95% CI:1.16‐5.38). Median and 5‐year overall survival (OS) for the entire cohort was 41.5 months (IQR:15.7‐107.8) and 39.8%, respectively. Of note, median OS incrementally worsened with increased ALBI grade: grade 1, 49.6 months (IQR:18.3‐NR) vs grade 2, 29.6 months (IQR:12.6‐98.4) vs grade 3, 16.9 months (IQR:6.5‐32.4; P  < 0.001). On multivariable analysis, higher ALBI grade remained associated with higher hazards of death (grade 2/3: hazard ratio = 1.36, 95% CI:1.04‐1.78). Conclusion: The ALBI score was associated with both short‐ and long‐term outcomes following resection for ICC and could prove a useful surrogate marker to identify patients at risk for adverse outcomes.